Aplicaciones catalíticas de oligonucleótidos modificados - Dellafiore, María Andrea (2017)
Oligonucleotides whose function is associated with catalytic or molecular recognition processes\nare known as functional oligonucleotides (ribozymes, DNAzymes, aptamers) and their applications\ninclude gene silencing therapy, diagnostic tools and sensor development, biocatalysis and\nnanotechnology.\nIn this work, we studied how to optimize the use of these oligonucleotides by incorporating\nchemical modifications.\nInitially, we studied the modulating effect of 2'-deoxy-2'-C-methylpyrimidin nucleosides on:\nthe hydrolytic activity and stability in biological media of 8-17 DNAzyme when incorporated in\ndifferent positions of their catalytic core; the silencing potency and specificity of siRNAs when\nincorporated in different positions of the antisense and sense strands; the thermodynamic stability\nof duplex and i-motif-forming DNA.\nFinally, the study was extended to the peroxidase DNAzyme using a fully modified sequence\nwith L-nucleotides and also an immobilized sequence testing a wide repertoire of substrates,\nincluding sulfides and paracetamol.